2015
DOI: 10.14710/bioma.17.1.9-15
|View full text |Cite
|
Sign up to set email alerts
|

Indeks Keragaman Serangga Hama Pada Tanaman Padi (Oryza sativa L.) Di Lahan Persawahan Padi Dataran Tinggi Desa Sukawening, Kecamatan Ciwidey, Kabupaten Bandung

Abstract: Kemampuan Indonesia dalam memenuhi kebutuhan beras nasional sangat penting. Akan tetapi, usaha pemenuhan kebutuhan beras ini tidak selamanya berjalan dengan lancar karena terganggunya produktivitas padi. Salah satu penyebab turunnya produktivitas padi di Indonesia karena adanya serangan serangga hama. Beberapa kendala yang menyebabkan gagalnya petani dalam mengendalikan serangga hama karena petani masih belum melakukan identifikasi serangga hama dan gejala serangan dengan baik. Penelitian yang dilaksanakan akh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
(1 reference statement)
2
0
0
Order By: Relevance
“…In this phase is the process of formation and growth of insects and insect populations not get enough food because of the abundance of the sorghum crop is still in the early growth so that it causes a type of insect that is not much. This is in line with research [7] of rice paddy crop diversity index, stating that the first observation of rice insect age of 2 weeks, the number of insects show the lowest number since they process the population growth.…”
Section: Number and Insects Species Caughtsupporting
confidence: 88%
See 1 more Smart Citation
“…In this phase is the process of formation and growth of insects and insect populations not get enough food because of the abundance of the sorghum crop is still in the early growth so that it causes a type of insect that is not much. This is in line with research [7] of rice paddy crop diversity index, stating that the first observation of rice insect age of 2 weeks, the number of insects show the lowest number since they process the population growth.…”
Section: Number and Insects Species Caughtsupporting
confidence: 88%
“…2 0 3 2 2 1 0 11 Ichneumoidae 0 0 0 2 3 2 0 7 Formicidae 8 7 17 14 32 25 19 15 137 Tiphiidae 0 0 1 0 2 0 2 5 Vespidae 0 0 0 0 2 1 6 16 Lepidoptera Noctuidae 0 0 2 4 3 1 2 12 Satyridae 1 0 0 1 2 1 1 6 Danaidae 0 0 0 0 0 1 2 5 Odonata Libelluidae 2 3 5 3 3 6 6 35 Coenagrionidae 0 1 0 3 3 1 1 9 Orthoptera In observation VII and VIII was found that the number of insect populations identified decrease from previous observations, this occurs because of sorghum as a food source of these insects has reached a stage of hardening seeds and physiologically mature, so the food source of some insects are not appropriate as previously, Oka (1995) in [9] states population density is governed by factors such as competition between individuals, chemical changes due to the secretion and metabolism, lack of food, predators/parasites, emigration. It is also in line with research [7] on rice plants, decrease the insect population at a late stage generative plant growth due to hardening of the tissues of the plant, so the condition is not preferred insect pests.…”
Section: Number and Insects Species Caughtsupporting
confidence: 75%